Comparison of acidic deep eutectic solvents in production of chitin nanocrystals. (15th May 2020) - Yuan, Yang; Hong, Shu; Lian, Hailan; Zhang, Kaitao; Liimatainen, Henrikki
Highlights: Efficient hydrolysis of chitin in organic acid deep eutectic solvent (DES). Physicochemical properties of ChNCs were compared prepared with different acidic DESs. Choline chloride and lactic acid DES is optimal choice in making lactate ChNCs. Green and fast production of ChNCs in lactic acid DES with yield up to 87.5 %. Abstract: Five different acidic deep eutectic solvents (DESs) composed of choline chloride and organic acids were applied to fabricate chitin nanocrystals (ChNCs). All DESs resulted in high transmittance and stable ChNCs suspensions with very high mass yield ranging from 78 % to 87.5 % under proper reaction conditions. The acidic DESs had a dual role in ChNCs fabrication, i.e. they promoted hydrolysis of chitin and acted as an acylation reagent. Physicochemical characterization of chitin revealed that the removal of amorphous area during DES treatments led to increased crystallinity of ChNCs and a dimension diversity correlated the DES used. The average diameter and length of individual ChNCs ranged from 42 nm to 49 nm and from 257 nm to 670 nm, respectively. The thermal stability of ChNCs was comparable to that of pristine chitin. Thus, acidic DESs showed to be non-toxic and environmentally benign solvents for production of functionalized chitin nanocrystals.